En opplyst samtale: Om rettsvitenskapens oppgaver i kriminalpolitikken - Holmboe, Morten (Nordisk Tidsskrift for Kriminalvidenskab, 2016)
English title: Title in English: An enlightened public discourse: On the tasks of legal research regarding criminal politics What are the primary tasks of legal research regarding the politics of crime? Political decisions on crime are decided and executed by politicians, the courts and administrators. Researchers should not avoid politically hot issues, but must take care not to let their political sympathies influence their statements when they give opinions qua legal experts. Academic freedom implies a duty for researchers to take part in enlightened public debates.